Insurance claim settlement delays and their consequences for service quality and financial management - Erry Donneli (Journal of Economic, Business & Accounting Research, 2026)
Background: Delays in health insurance claim payments remain a persistent challenge for healthcare providers in Indonesia, particularly private clinics that rely heavily on insurance reimbursements for operational sustainability. Methods: This study employed a qualitative case-study approach at MMC using in-depth interviews with clinic managers, administrative staff, and medical personnel, supported by document analysis of insurance claims data from 2022–2023. Data were analyzed using thematic coding and triangulation techniques. Findings: The results indicate a declining proportion of claims paid within the agreed settlement period (N-1, defined as claims settled within one month after submission), alongside a significant increase in delayed claims, including claims settled after two months (N-2) and those exceeding two months (>N-2). Claim payment delays were primarily caused by incomplete medical records, limited administrative capacity, inadequate management information systems, and financial constraints on the insurer’s side. These delays disrupted clinic cash flow, delayed staff salary payments, constrained drug availability, and negatively affected service quality. Conclusion: Late payment of health insurance claims significantly undermines both financial stability and service quality at MMC (a private healthcare clinic in Mataram City, Indonesia). Strengthening administrative capacity, improving medical documentation completeness, and optimizing clinic–insurer coordination are critical strategies to mitigate claim delays and ensure sustainable healthcare service delivery. Novelty/Originality of this article: This study contributes novel insights by explicitly linking claim-settlement time categories (claims settled within one month, two months, and more than two months) with service quality implications at the clinic level, providing empirical evidence from Indonesia’s private healthcare sector.